Validation and Testing of Initial and In-Situ Mutual Coupling-Based Calibration of a Dual-Polarized Active Phased Array Antenna - Rodrigo M. Lebron; Pei-Sang Tsai; Jonathan M. Emmett; Caleb Fulton; Jorge L. Salazar-Cerreno (IEEE Access, 2020)
This paper presents experimental results of an initial and in-situ mutual coupling calibration techniques of an active phased array antenna. The antenna is a dual-polarized 64-element C-band subarray panel equipped with an RF beamformer that enables mutual coupling measurements. Both techniques were implemented, tested and validated using a custom anechoic chamber and a radar backend. The implementation of a radar backend enables the in-situ validation of both methods. A conventional near-field calibration procedure, also known as park and probe, was used as a reference, in order to validate the proposed method. To quantify the calibration effectiveness of the mutual coupling-based techniques, the results are translated into phase and amplitude errors. It is found that the amplitude estimation of the tested initial technique is affected by edge effects, resulting in errors larger than 1 dB, whereas the phase estimation is less sensitive, yielding an overall root mean square error (RMSE) of 2.5°. In contrast, the proposed in-situ technique is not affected by edge effects, and its estimation RMSE is less than 0.12 dB in amplitude and less than 0.75° in phase. Mutual coupling-based calibration techniques are demonstrated to be very versatile, as they provide calibration methods for environments outside an anechoic chamber, and they also enable immediate feedback on the health of the system.